ANALISIS PEMANFAATAN HYPNOTHERAPY UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MASA COVID-19 DI SMP SANTO LUKAS II JAKARTA UTARA - Andreas Alentus; Mesta Limbong; Witarsa Tambunan (Jurnal Manajemen Pendidikan, 2022)
The implementation of this research is to find out to how far the results of using hypnotherapy techniques can improve the learning achievement of students of SMP Santo Lukas II, North Jakarta, who have decreased learning achievement due to the influence of the Covid-19 outbreak. This study used a qualitative approach with a total of 5 participants as research subjects. Analysis of data derived from documentation data, both leger and report cards as well as counseling notes as well as the results of interviews with family informants and school management, can provide a clear picture of the impact of the Covid-19 outbreak on participants' learning achievement as well as the results of using hypnotherapy techniques to increase achievement. participant study. The results showed that the COVID-19 outbreak had a very significant effect on the decline in student achievement at SMP Santo Lukas II, North Jakarta. However, after being treated using hypnotherapy techniques, it showed that the participants had progressed in their learning achievements. After hypnotherapy was carried out, the changes were very significant for five subjects and continued to increase.